Exploring the Interdependence Between Visually Impaired and Sighted People in the Early Phase of Friendship - Nurjaman, Tabah Aris (The Center for Disability Studies and Services Brawijaya University, 2018)
A person with visual impairment must resist anatomic, social, and cultural obstruction thus requiring other individuals to complete the activities that require a sense of sight. This situation encourages them to establish relations of friendship with sighted people, which is considered to be always present in whenever needed help. The existence of aid distribution indicates the idiosyncrasies of friendship between visual impairment and sighted people, as also indicates a tendency of dependencies. Thus, this study aims to explore the relationship patterns of interdependence in the early phase of friendship. This study used a qualitative method with descriptive phenomenology approach. This study uses in-depth interviews at the data collection stage involving six research informants; or three couples of friends. The credibility of the research uses the triangulation (significant other) and member checking. The underlying aspects of the establishment of friendship in the study include contact, appraisal, and instrumental activity assistance on the visually impaired party; as well as contact, attractiveness, and instrumental aid distribution on the sighted party. The aspect of instrumental aid distribution is idiosyncratic in this friendship. Frequentative instrumental aid distribution indicates the tendency of dependence on visually impaired party, as well as reflecting the entity of help on sighted party which directs the interdependence pattern relationship. Periodic instrumental aid distribution indicates the tendency of independence on visually impaired party, as well as reflecting the entity of altruism on sighted party which directs the independence pattern relationship.